2020
DOI: 10.3390/molecules25184190
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Extracts of Hibiscus acetosella (Cranberry Hibiscus) and Their Antioxidant and Antibacterial Properties

Abstract: Hibiscus species are rich in phenolic compounds and have been traditionally used for improving human health through their bioactive activities. The present study investigated the phenolic compounds of leaf extracts from 18 different H. acetosella accessions and evaluated their biofunctional properties, focusing on antioxidant and antibacterial activity. The most abundant phenolic compound in H. acetosella was caffeic acid, with levels ranging from 14.95 to 42.93 mg/100 g. The antioxidant activity measured by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The data on antibacterial activity of ethanolic extracts corroborated negative correlations between TPC and the growth of B. subtilis , S. aureus , and P. aeruginosa , and also between TAC and the growth of B. subtilis , P. aeruginosa and S. enterica . Comparable results were reported by some other studies, where negative correlations were also observed between TPC and TAC levels and activities of S. aureus and P. aeruginosa [ 33 ], or correlation was not significant [ 34 ]. We can presume that the stronger antibacterial effect of ethanol extracts was due to other biologically active compounds.…”
Section: Resultssupporting
confidence: 85%
“…The data on antibacterial activity of ethanolic extracts corroborated negative correlations between TPC and the growth of B. subtilis , S. aureus , and P. aeruginosa , and also between TAC and the growth of B. subtilis , P. aeruginosa and S. enterica . Comparable results were reported by some other studies, where negative correlations were also observed between TPC and TAC levels and activities of S. aureus and P. aeruginosa [ 33 ], or correlation was not significant [ 34 ]. We can presume that the stronger antibacterial effect of ethanol extracts was due to other biologically active compounds.…”
Section: Resultssupporting
confidence: 85%
“…ABTS scavenging activity of different extracts of hop cone was determined as described previously [ 31 ]. The ABTS reagent was prepared by mixing 5 mL of 7 mM ABTS with 88 μL of 140 mM potassium persulfate.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a study on H. esculentus showed the in vitro antioxidant potential of quercetin derivatives and catechins present in its extracts [ 61 ]. Finally, in H. acetosella , the antioxidant activity was strongly correlated with the anthocyanins content [ 62 ].…”
Section: Resultsmentioning
confidence: 99%